Resource dependence theory: How well does it explain behavior of organizations? - Werner Nienhüser (Management Revue, 2008)
This article evaluates to what extent Resource Dependence Theory (RDT) is able to explain organizational processes and structures. The evaluation criteria are the empirical corroboration of the theory, its information content and generality, but also how realistic the assumptions of the RDT are. The evaluation shows that the theory is empirically well confirmed. On the whole, Resource Dependence Theory significantly contributes to explaining behavior, structure, stability, and change of organizations.
Keywords: 650; Resource Dependence Theory; power; behavior of organizations